Knowledge of nursing students about central venous catheters - Mlinar Suzana; Rašković-Malnaršić Rosanda (Vojnosanitetski Pregled)
Background/Aim. Central venous catheters (CVC) are at the crucial importance, particulary in the intensive therapy units. In order to handle a CVC safely, nursing students need to acquire theoretical and practical knowledge during the course of their studies. The aim of the study was to establish theoretical knowledge of nursing students about the procedures of nurses in placing and removing a central venous catheter (CVC), dressing the catheter entry point, the reasons for measuring central venous pressure (CVP), possible complications and risk factors for developing infections related to CVC. Methods. The questionnaire developed specifically for this cross-sectionl study was handed out to 87 full-time students and 57 part-time students. Results. The results show that all the surveyed nursing students know why chest radiography is carried out when inserting a catheter, have relatively good knowledge of CVC insertion points, procedures carried out in case of a suspected catheter sepsis and complications and risk factors for the development of infections related to CVC. However, the study show that the majority of students have insufficient knowledge of the procedures accompanying insertion of a catheter, signs that indicate correct functioning of CVC, frequency of flushing a catheter when it is not in use and the reasons for introducing an implanted CVC. Conclusion. Based on the results of the study it can be concluded that the second-year nursing students have insufficient knowledge of CVC. In order to correctly and safely handle a CVC, good theoretical knowledge and relevant practical experience are needed. The authors therefore believe that, in future, the classes should be organized in smaller groups with step-by-step demonstrations of individual procedures in handling a CVC, and the students encouraged to learn as actively as possible.